Study on the eye movement characteristics of the badminton practitioners of different levels regarding visual attention - Chen, Yanlan; Zulnaidi, Hutkemri; Syed Ali, Syed Kamaruzaman Bin (Frontiers in Psychology, 2023)
Badminton is a highly sophisticated tactical and tactical game that is fierce and competitive. It requires the same action to hit the ball with different landing points. Therefore, the complexity of sports decision-making is relatively high. It is very important to study the difference between the eye movement characteristics of different levels of badminton athletes and the difference of the eye movement characteristics that athletes pay attention to at different sports level. In this study, 15 students from the badminton professional training team of the Physical Education College of Jiangxi Science and Technology Normal University and 15 students from the common public sports and badminton course were taken as the experimental objects. The experimental test of the virtual sports situation of badminton in the laboratory was conducted by using the eye tracker. The eye movement index of the students was recorded for statistical analysis, and the following results were obtained: 1.In the cognitive decision masking task, the reaction time of the professional badminton practitioners was faster than that of the amateur badminton practitioners. In the intuitive decision masking task, the reaction time and accuracy of the professional badminton practitioners were faster than those of the amateur badminton practitioners. 2.The professional badminton practitioners were able to process and integrate the searched information in the process of attention selection information, while the amateur practitioners were passive, able to search and filter information, but did not have the ability to actively process and integrate the searched information. 3. Badminton practitioners in the professional group can reasonably allocate their attention and process information in the process of attention transfer, while those in the amateur group are easily affected by external interference factors. The motor intelligence level of badminton practitioners in the professional group was higher than that in the amateur group. The badminton practitioners in the two groups of different levels had attention transfer, and the professional group was more able to allocate attention and process information reasonably in the process of attention transfer. 4. The mental skills of the professional badminton practitioners were higher than those of the amateur badminton practitioners.